Virtuality and Academic Performance in Higher Education for adults during COVID-19 times - Romero-Escalante, Victor Fabian (Revista Complutense de Educación, 2024)
Introduction. The emergency remote teaching modality in university programs for adults due to the pandemic has generated a radical change in the academic life of students, who over time have managed to adapt to virtuality. The aim of this study was to determine the degree of relationship between the perception of the emergency remote education modality and the academic performance of students in the adult education during the COVID-19 pandemic. Method. The research approach was quantitative with a non-experimental design and correlational level. The sample consisted of 194 students, who were provided with an adapted questionnaire that measures the perception of teaching, which demonstrated validity and reliability. Additionally, final grade transcripts were used for academic performance. Results and Discussion. The main finding was the adaptation of the students to the new modality, concluding that there is a direct and significant relationship (Sig.= .000; Rho.= .665) between the studied variables.